2021
DOI: 10.1177/0265407521991925
|View full text |Cite
|
Sign up to set email alerts
|

Technology use during couples’ bedtime routines, bedtime satisfaction, and associations with individual and relational well-being

Abstract: In this study, we examined the typical and ideal bedtime routines of 289 Americans in cohabiting relationships who were recruited from Amazon’s Mechanical Turk. Participants described their bedtime routines, indicated their frequency of sex with their partner, and completed surveys measuring their bedtime, sexual, relationship, and life satisfaction. There were some incongruencies between ideal and typical scenarios, with joint activities (both technological and non-technological) featured more often in the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Research of co-present phone use in couple relationships has revealed that when romantic partners spend time together, they often show one another what they see and do on the phone, and such shared phone use is viewed as a positive experience (Kelly et al, 2017). Although McDaniel et al (2021) noted that the positive relational implications of shared technology use were not robust, Drouin and McDaniel (2021) found consistent positive associations between shared technology use and various forms of satisfaction in couple relationships. Benefits have also been identified in adolescent friendships-using computers with friends predicts better friendship quality, likely because it provides opportunities for social exchanges and self-disclosure (Desjarlais & Willoughby, 2010).…”
Section: Contextual Factors As Moderators: Phone Sharing and Seriousn...mentioning
confidence: 99%
“…Research of co-present phone use in couple relationships has revealed that when romantic partners spend time together, they often show one another what they see and do on the phone, and such shared phone use is viewed as a positive experience (Kelly et al, 2017). Although McDaniel et al (2021) noted that the positive relational implications of shared technology use were not robust, Drouin and McDaniel (2021) found consistent positive associations between shared technology use and various forms of satisfaction in couple relationships. Benefits have also been identified in adolescent friendships-using computers with friends predicts better friendship quality, likely because it provides opportunities for social exchanges and self-disclosure (Desjarlais & Willoughby, 2010).…”
Section: Contextual Factors As Moderators: Phone Sharing and Seriousn...mentioning
confidence: 99%
“…It appears that when adolescents have a social goal for digital social multitasking, phone use becomes a complement, rather than a distraction, of the face‐to‐face interaction. Indeed, copresent technology use can be an enjoyable experience and a relationship facilitator when the copresent individuals use the technology together or engage each other in the use (Drouin & McDaniel, 2021; Kelly et al, 2017). It is plausible that when adolescents are motivated to perform digital social multitasking for social reasons, they involve each other in the phone‐based activity (e.g., C. Yang & Christofferson, 2020); the focus is the connection rather than the phone, making problematic use less of a concern.…”
Section: Discussionmentioning
confidence: 99%
“… McDaniel & Drouin, 2019 ), highlighting its negative influence on relationship quality, little is known about its antecedents (and, to our knowledge, if it has done so, it has mainly used one-time assessments; e.g. Drouin & McDaniel, 2021 ). Our work takes the wider context into consideration, highlighting how outside factors — those associated with the COVID-19 pandemic — are related to greater technology use.…”
Section: Discussionmentioning
confidence: 99%